Large hemorrhage due to venipuncture in the elbow of a patient with severe hemophilia: A case report and literature review - LYU, JINGTONG (Exp Ther Med, 2016)
Hemophilia A, which is the most common form of hemophilia, is caused by a deficiency of clotting factor VIII. The incidence of hemophilia A is 1:10,000 people worldwide. The most common complication associated with hemophilia A is bleeding into joints, predominantly the knees, ankles, and elbows, which may lead to destruction or osteoarthritis of the specific joint. Various degrees of disability may follow these initial or recurrent hemorrhages. Subsequent to improvements in medical management, patients with hemophilia A currently have a life expectancy similar to that of the normal population. However, the management of patients with hemophilia A remains a clinical challenge for various reasons, including the lack of reliable and cost-effective treatment, and the high risk of intra- or post-operative hemorrhages. Large hemorrhages due to the phlebotomizing of young patients are very rare. To the best of our knowledge, the present case is the first report regarding the occurrence of a large hemorrhage due to venipuncture in the elbow of a patient with hemophilia A, and discusses the pathogenesis, clinical manifestation, and the medico-chirurgical treatment of this patient.